Ocular Toxocariasis in The Anterior Chamber of The Eye: Poster Presentation - Case Report - Resident - Chandra, Monica Camilla; MD, Anne Umboh,; Rares, MD, Laya (Majalah Oftalmologi Indonesia, 2023)
Introduction : Ocular toxocariasis (OT) is a zoonotic infection caused by Toxocara canis and Toxocara cati. Dogs and cats, the definitive hosts of the roundworm, pass unembryonated eggs via their feces into the environment (often into the soil). Transmission to humans occurs through ingestion of soil or contaminated food, or the fecal– oral route. Case Illustration : A 14 years old male presented with pain and redness in the right eye 2 months prior to the visit. Complaints are redness, itching, and pain especially in the night on the right eye. The patient had habits of eating raw meat and walking around in dirt without any footwear. Ophthalmologic examination showed a toxocara sp. larvae in the anterior chamber of the right eye. This patient treated with surgical removal of the worm, given antihelminth and topical corticosteroid. Discussion : Toxocariasis results from infection with Toxocara cati (an intestinal parasite of cats) or Toxocara canis (an intestinal parasite of dogs). Children acquire the disease by close association with pets and by eating dirt (pica) contaminated with Toxocara ova. The ingested ova form larvae that penetrate the intestinal mucosa and gain access to the systemic circulation and finally to the eye. Systemic or local corticosteroids should be given when there is evidence of significant intraocular inflammation. Conclusion : This case described a patient who was diagnosed with a living worm as foreign bodies in the right eye.